Overcoming Time Inconsistency with a Matched Bet: Theory and Evidence from Exercising - Andrej Woerner (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper introduces the matched-bet mechanism. The matched bet is an easily applicable and strictly budget-balanced mechanism that aims to help people overcome time-inconsistent behavior. I show theoretically that offering a matched bet helps both sophisticated and naive procrastinators to reduce time-inconsistent behavior. A field experiment on exercising confirms the theoretical predictions: offering a matched bet has a significant positive effect on gym attendance. Self-reported procrastinators are significantly more likely to take up the matched bet. Overall, the matched bet proves a promising device to help people not to procrastinate.
Keywords: C93; D47; F90; I12; 330; monetary incentives; market design; field experiment; health behavior